Caption Contest (The Biblical archaeology review, 2025)
"Weren’t we predicted to win hands down?" —Andy Magid, Norman, Oklahoma Thank you to all those who submitted caption entries for our Fall 2024 cartoon, based on Exodus 17:11-12: "Whenever Moses held up his hand, Israel prevailed; and whenever he lowered his hand, Amalek prevailed. But Moses’ hands grew weary; so they took a stone […]